Pengujian Performa Kampas Rem Non Asbes Variasi Calcium Carbonate Dengan Perekat Phenolic Resin - Supriyanto, Supriyanto, Bambang Waluyo F, ST. MT (2016)
Brake is one component of a motor vehicle that serves to slow or stop the vehicle, especially a ground vehicle. Especially when a high-speed vehicle brake function has an important role, even human lives depend on the efficacy of the brake lining material. It would require a special design on the canvas material. The materials used in this study is the aluminum powder, carbon powder, fiberglass fibers, brass powder, graphite, barium sulfate, CaCO3 and phenolic resins as a binder. Manufacture of brake pressed with a load of 7.5 tons for 7 minutes, sintering for 60 minutes with a temperature of 200 ° C. Tests performed include Digital Shore Durometer hardness test and friction test. From the research data hardness and friction is known that affect the price of CaCO3 powder hardness and wear canvas specimens, which varied from CaCO3 powder weighing 3 grams, 4 grams and 5 grams of the most excellent power ie CaCO3 powder weighing 3 grams. However, the wear rate is still higher than the canvass Indopart.